Enzymatic Resolution of α‐Methyleneparaconic Acids and Evaluation of their Biological Activity. Issue 3 (9th January 2015) - Chakrabarty, Kuheli; Defrenza, Ivana; Denora, Nunzio; Drioli, Sara; Forzato, Cristina; Franco, Massimo; Lentini, Giovanni; Nitti, Patrizia; Pitacco, Giuliana
ABSTRACT Both enantiomers of three biologically relevant paraconic acids—MB‐3, methylenolactocin, and C75—were obtained with enantioselectivities up to 99% by kinetic enzymatic resolutions. Good enantiomeric excesses were obtained for MB‐3 and methylenolactocin, using α‐chymotrypsin and aminoacylase as enantiocomplementary enzymes, while C75 was resolved with aminoacylase. They all were evaluated for their antiproliferative, antibacterial, and antifungal activities, showing weak effects and practically no difference between enantiomers in each case. At high concentrations (16–64 µg/mL), (–)‐ C75 acted as an antimicrobial agent against Gram‐positive bacteria. Chirality 27:239–246, 2015. © 2015 Wiley Periodicals, Inc.